HAMBATAN BELAJAR SISWA PADA MASA PANDEMI COVID-19 DI MA MA’ARIF 06 PASIR SAKTI LAMPUNG TIMUR - Janah, Siti Roikatul (AS-SALAM, 2020)
This article aims to describe the barriers to student learning during the Covid-19 pandemic at MA Maarif 06 Pasir Sakti, East Lampung. The research used a qualitative descriptive method with data sources of teachers, homeroom teachers, students and parents. The result of this determination is that there are several obstacles faced by students, teachers and parents in teaching and learning activities in the Covid-19 Pandemic Era, namely the addition of internet quota costs, communication and socialization between students, teachers and parents is reduced and working hours which becomes unlimited for teachers because they have to communicate and coordinate with parents, other teachers, and principals. The positive contribution of the results of this study is the spread of information regarding the urgency of mastery of technology to support every activity carried out by humans, one of which is in the realm of education to be able to compete globally.